Physical properties of soil in the early stage of an agroforestry system in the High Andean zone - Muñoz-Rodríguez, Martin Alonso; Delgado-Vargas, Iván Andrés; Guerrero, Jennyfer Cristina; Andrade, Anyi Valeria (Revista de Ciencias Agrícolas, 2020)
In Nariño, Colombia, land use has generated some problems such as erosion, compaction, lack of fertility, among others, so it is necessary to search for alternatives to mitigate these impacts. The objective of this study was to evaluate some physical properties of the soil in an agroforest system with Morella pubescens (Humb. & Bonpl. ex Willd.) Wilbur with Smallanthussonchifolius (Poepp.) H.Rob, in the experimental farm of Botana, in the city of Pasto, Nariño, where the bulk density, real density, total porosity, structural stability properties and distribution of aggregates were analyzed. The datas were obtained in two phases: f1 and f2 before and after agroforestry system implementation, respectively. A randomized complete block design with three treatments and three replications were used. The treatments corresponded to plant densities, T1: S sonchifoliuos, sowed to 1x1m, T2:0.8x0.8m y T3:0.5x0.5m, with three replications. M pusescens was stablished to 4x4m between plants and 9 m between rows and the control (f1). The statistics have differences between f1 (control) and f2 (treatments), to the structural stability properties and distribution of aggregates. The ground suffered a structural stability change to stable lightly (0.97 D.P.M) in f1 to a stable moderate (2.53 D.P.M), in f2. The distribution of aggregates passed to 60% in f1 to 70.3% in f2, with a media aggregation status. The different agroforest systems management could help, in the long term, by improving the structure of the ground through the vegetal material of arboreal component, the application of a minimum farming and the addition of organic matter.